Pengaruh Brand Image, Perceived Quality, dan eWOM terhadap Purchase Intention Mobil di Jakarta - Anastasia Kristinawati; Keni Keni (Universitas Tarumanagara, 2021)
The research aims to find out the influence of brand image, perceived quality and eWOM to purchase intention of car in Jakarta. The sampling method used in the study is non probability sampling by convenience sampling. The sample in this research is 150 respondents. 150 valid data were analysed using structural equaltion modelling to test hypothesizes in the research. Based on analysis, all variables which is brand image, perceived quality and eWOM have positif significant effect to purchase intention. Perceived quality is the most influencing factor to purchase intention. Based on findings, researcher suggested the company to focus on perceived quality. Customers think good car performance, good product quality and promising warranty as a good perceived quality. Penelitian ini memiliki tujuan untuk mengetahui pengaruh brand image, perceived quality dan eWOM terhadap purchase intention mobil di Jakarta. Penelitian ini menggunakan non-probability sampling dengan teknik convenience sampling. Sampel yang digunakan dalam penelitian ini berjumlah 150 responden. 150 data yang valid dianalisa menggunakan structural equation modelling untuk menguji hipotesis. Berdasarkan hasil penelitian, semua variabel yaitu brand image, perceived quality dan eWOM memiliki pengaruh positif signifikan terhadap purchase intention. Perceived quality merupakan faktor yang paling berpengaruh terhadap purchase intention. Dari hasil ini, peneliti menyarankan agar perusahaan fokus pada perceived quality. Pelanggan menilai performa yang baik, kualitas produk baik dan garansi yang menjanjikan sebagai perceived quality yang baik.